Expression of gamma interferon by simian immunodeficiency virus increases attenuation and reduces postchallenge virus load in vaccinated rhesus macaques. - Giavedoni, L (1997)
Simian immunodeficiency virus (SIV) infection of macaques is a model for human immunodeficiency virus (HIV) infection. We have previously reported the construction and characterization of an SIV vector with a deletion in the nef gene (SIV(delta nef)) and expressing gamma interferon (SIV(HyIFN)) (L. Giavedoni and T. Yilma, J. Virol. 70:2247-2251, 1996). We now show that rhesus macaques vaccinated with SIV(HyIFN) have a lower viral load than a group similarly immunized with SIV(delta nef). Viral loads remained low in the SIV(HyIFN)-vaccinated group even though SIV expressing gamma interferon could not be isolated after 6 weeks postimmunization in these animals. All immunized and two naive control macaques became infected when challenged with virulent SIV(mac251), at 25 weeks postvaccination. In contrast to the two naive controls that died by 12 and 18 weeks postchallenge, all vaccinated animals remained healthy for more than 32 weeks. In addition, postchallenge cell-associated virus load was significantly lower in SIV(HyIFN)-immunized animals than in the group vaccinated with SIV(delta nef). These findings indicate that cytokine-expressing viruses can provide a novel approach for development of safe and efficacious live attenuated vaccines for AIDS.